2022
DOI: 10.1007/s11065-022-09537-4
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour Change Techniques in Computerized Cognitive Training for Cognitively Healthy Older Adults: A Systematic Review

Abstract: We aimed to describe behaviour change techniques (BCT) used in trials evaluating computerised cognitive training (CCT) in cognitively healthy older adults, and explore whether BCTs are associated with improved adherence and efficacy. The 90 papers included in a recent meta-analysis were reviewed for information about adherence and use of BCTs in accordance with the Behaviour Change Taxonomy. Studies using a specific BCT were compared with studies not using that BCT on efficacy (difference in Hedges’ g [Δg]) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 108 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…Expectations and beliefs about the outcomes of CCT may affect training motivation and engagement (Tetlow and Edwards, 2017). Peeters et al (2023) reported on Behaviour Change Techniques (BCT) of CCT from 88 studies with cognitively healthy adults. There are 93 individual techniques in COM-B falling into 16 clusters or categories (Michie et al, 2015).…”
Section: Behaviour Change Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…Expectations and beliefs about the outcomes of CCT may affect training motivation and engagement (Tetlow and Edwards, 2017). Peeters et al (2023) reported on Behaviour Change Techniques (BCT) of CCT from 88 studies with cognitively healthy adults. There are 93 individual techniques in COM-B falling into 16 clusters or categories (Michie et al, 2015).…”
Section: Behaviour Change Theorymentioning
confidence: 99%
“…Studies using "graded tasks" had lower adherence. Self-reported barriers to adherence included excessive time commitment, health problems, lack of interest or motivation, holiday/travel, and lack of time (Peeters et al, 2023).…”
Section: Behaviour Change Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The respective incidence, mortality, and disability-adjusted life year (DALY) rates of dementia in China increased from These variables cause 40% of dementia in China, 41% in India, and 56% in Latin America [7]. Neurology researchers have revealed that cognitive therapies for middle-aged and older adults can remodel nerves like the cerebral cortex and hippocampus, which are critical for learning, memory, and cognition [8].…”
Section: Introductionmentioning
confidence: 99%